2019
DOI: 10.1186/s13058-019-1183-3
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging for characterizing tumor microstructure and improving diagnostic performance on breast MRI: a prospective observational study

Abstract: Background Diffusion-weighted imaging (DWI) can increase breast MRI diagnostic specificity due to the tendency of malignancies to restrict diffusion. Diffusion tensor imaging (DTI) provides further information over conventional DWI regarding diffusion directionality and anisotropy. Our study evaluates DTI features of suspicious breast lesions detected on MRI to determine the added diagnostic value of DTI for breast imaging . Methods With IRB approval, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 49 publications
5
36
0
Order By: Relevance
“…While the DTD-derived mean shape E[ D ∆ 2 ] also reports on tissue anisotropy, it does so without being influenced by the orientational order of fibrous tissues at the sub-voxel scale (quantified by the orientational order parameter OP). We found significantly higher mean values of FA and E[ D ∆ 2 ] in tumors compared to FGT, agreeing with the previous literature on FA [ 55 , 65 ], which indicates that both metrics could be appropriate for breast cancer diagnosis. However, the mean shape E[ D ∆ 2 ] appears to be a more reliable metric than FA, as shown by its higher values in tumors with low OP and its higher statistical power for distinguishing tumors and FGT ( p < 0.001 for E[ D ∆ 2 ] versus p = 0.02 for FA).…”
Section: Discussionsupporting
confidence: 92%
“…While the DTD-derived mean shape E[ D ∆ 2 ] also reports on tissue anisotropy, it does so without being influenced by the orientational order of fibrous tissues at the sub-voxel scale (quantified by the orientational order parameter OP). We found significantly higher mean values of FA and E[ D ∆ 2 ] in tumors compared to FGT, agreeing with the previous literature on FA [ 55 , 65 ], which indicates that both metrics could be appropriate for breast cancer diagnosis. However, the mean shape E[ D ∆ 2 ] appears to be a more reliable metric than FA, as shown by its higher values in tumors with low OP and its higher statistical power for distinguishing tumors and FGT ( p < 0.001 for E[ D ∆ 2 ] versus p = 0.02 for FA).…”
Section: Discussionsupporting
confidence: 92%
“…[33] showed that isotropic diffusivity in FGT (Ħ 2 × 10 −3 mm 2 /s) [139][140][141] were significantly higher than cancers which is in agreement with previous findings on MD [142][143][144][145]. [33] reported that the fractional anisotropy and microscopic anisotropy values in FGT were significantly lower than tumors, in line with the previous literature [139,146].In healthy breast tissue, there are elongated structures such as lobules, ducts, and stroma in FGT that have large diameters compared to the mean displacement of water molecules during the diffusion time [139]. This may lead to low microscopic anisotropy and FA values in healthy breast tissue.…”
Section: Breast Imagingsupporting
confidence: 89%
“…However, single diffusion encoding cannot provide detailed information on tumor microstructure. Therefore, DTI is performed with conventional breast MRI, and this enables the estimation of MD and FA, which is used to determine whether a breast lesion is benign or malignant (44)(45)(46). Furthermore, MK can be estimated using DKI.…”
Section: Discussionmentioning
confidence: 99%